(untitled) (Journal of Medical & Health Sciences Review, 2025)
Methicillin-Resistant Staphylococcus aureus (MRSA) is a major cause of healthcare-associated infections worldwide posing significant challenges due to its resistance to multiple antibiotics. This study focuses on the molecular characterization of S. aureus isolates collected from a tertiary care hospital in Faisalabad, Pakistan. A total of 200 clinical samples were obtained from various infection sites including blood, wound and skin lesions. The samples were cultured on Mannitol Salt agar. Phenotypically identification revealed that total 112 samples were declared as confirmed S. aureus colonies on the basis of gram stain and biochemical test. Antibiotic sensitivity testing (AST) performed by using Cefoxitin disc diffusion and modified Kirby-Bauer disk diffusion assays to assess the susceptibility pattern of isolated S. aureus against Methicillin and other antibiotics respectively. Out of which 55 (49.1%) were confirmed methicillin resistant strains. Molecular analysis was conducted to detect the presence of the mecA gene, a key determinant of methicillin resistance through PCR, DNA extraction and agarose gel electrophoresis techniques which suggested the prevalence of gene was (78.1%) in the methicillin resistant strains of S. aureus. The isolates showed significant resistance to frequently utilized antibiotics such as penicillin, cephalosporin and fluoroquinolones hence rendering these medications ineffectual for treating MRSA infections.